The Impact of Monetary Policy on Financial Markets in Small Open Economies : More or Less Effective During the Global Financial Crisis? - Pennings, Steven; Ramayandi, Arief; Tang, Hsiao Chink (Elsevier, 2016)
This paper estimates the impact of monetary policy on exchange rates and stock prices of eight small open economies: Australia, Canada, the Republic of Korea, New Zealand, the United Kingdom, Indonesia, Malaysia, and Thailand. On average across these countries in the full sample, a one percentage point surprise rise in official interest rates leads to a 1% appreciation of the exchange rate and a 0.5–1% fall in stock prices, with somewhat stronger effects in OECD countries than non-OECD countries (though differences are sometimes not significant). We find little robust evidence of a change in the effect of monetary policy surprises during the recent financial crisis.